Conceptual Spaces of the Immune System - Fierz, Walter (Frontiers in Immunology, 2016)
The immune system can be looked at as a cognitive system. This is often done in analogy to the neuro-psychological system. Here, it is demonstrated that the cognitive functions of the immune system can be properly described within a new theory of cognitive science. Gärdenfors’ geometrical framework of conceptual spaces is applied to immune cognition. Basic notions, like quality dimensions, natural properties and concepts, similarities, prototypes, saliences etc., are related to cognitive phenomena of the immune system. Constraints derived from treating the immune system within a cognitive theory, like Gärdenfors’ conceptual spaces, might well prove to be instrumental for the design of vaccines, immunological diagnostic tests, and immunotherapy.